Pengaruh Kepemimpinan dan Komunikasi Intern Terhadap Efektivitas Kerja Pegawai di FITK UIN Raden Fatah Palembang - Rusmaini, Rusmaini (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
Work effectiveness is the degree of achievement of an organization's goals based on the activities carried out. Work effectiveness is influenced by various factors including leadership, internal communication. The research objectives are: (1) to determine whether there is the influence of leadership and internal communication on work effectiveness (2) to find out how much influence leadership and internal communication have on employee work effectiveness both simultaneously and partially. The population of this study was employees of the Tarbiyah and Teacher Training Faculty of UIN Raden Fatah Palembang; it is 90 people. There are three variables studied in this study, namely: (1) leadership (2) internal communication (3) work effectiveness. Data collection methods used are questionnaires and documentation. The data analysis method used is the descriptive analysis of percentages and multiple linear regression analysis using SPSS for Windows Release 16. Based on the descriptive analysis, the percentage of leadership is 84.24% (very good category), the level of internal communication is 86% (very good category), while the level of work effectiveness is 78.78% (good category). Based on the calculation of multiple linear regression analysis also obtained F calculate of 17,234 with a significance of 0,000. Because the price of significance obtained is less than 0.05, the regression model obtained is significant. This means that the working hypothesis (Ha) is accepted, that is, there is the influence of leadership and internal communication on work effectiveness. The magnitude of the effect is simultaneously 28.4% while partially is 16% for leadership variables and 5.29% for internal communication. Based on the results of research, leadership and internal communication have a positive influence on work effectiveness. Leadership has a greater influence than internal communication.